2021
DOI: 10.1007/s00259-021-05412-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pretherapeutic osseous tumor volume and standard hematology for prediction of hematotoxicity after PSMA-targeted radioligand therapy

Abstract: Purpose Hematotoxicity is a potentially dose-limiting adverse event in patients with metastasized castration-resistant prostate cancer (mCRPC) undergoing prostate-specific membrane antigen (PSMA)-directed radioligand therapy (RLT). We aimed to identify clinical or PSMA-targeted imaging-derived parameters to predict hematological adverse events at early and late stages in the treatment course. Methods In 67 patients with mCRPC scheduled for 177Lu-PSMA-617 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Future studies investigating the hematologic side effects of [ 177 Lu]Lu-PSMA I&T should also include laboratory values related to lymphopenia or neutropenia. In addition, correlation of pretherapeutic tumor burden with detailed hematological laboratory values during follow-up would then be possible [24].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies investigating the hematologic side effects of [ 177 Lu]Lu-PSMA I&T should also include laboratory values related to lymphopenia or neutropenia. In addition, correlation of pretherapeutic tumor burden with detailed hematological laboratory values during follow-up would then be possible [24].…”
Section: Discussionmentioning
confidence: 99%
“…Most RCTs showed small proportions with severe hematological adverse effects. A study indicated that a pretreatment hematological impairment contributed to the proportion of patients with severe hematological adverse effects after L3 treatment with PRLT [46]. The TheraP trial reported several categories for the premature discontinuation of the treatments [19], so the trial had a lower rate of patients who discontinued L3 treatment due to adverse effects than other RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment was performed following established procedure guidelines, with RLT cycles repeated every 6-8 weeks (median, 42 days [IQR, 42 to 43] [8]. Prior to the first and at each cycle, a standard laboratory panel, including blood cell counts, liver enzymes, and PSA was also assessed [25].…”
Section: [ 177 Lu]lu-psma-iandt Rltmentioning
confidence: 99%